Financial Wellbeing Among Public and Private Sector Employees: A Preliminary Study - Sehrawat, Kanchan; Vij, Madhu (Indian Journal of Finance, 2020)
Financial wellbeing of an individual is an important component of overall financial wellbeing. Further, financial wellbeing has often been linked to the job performance and efficiency of the employee. Hence, financial wellbeing is not only important for individuals, but also for their organization and country at large. The current study utilized 105 valid survey responses collected during December 2018 from private and public sector employees in NCT of Delhi, India. The study further examined the level of perceived financial wellbeing (FWB), financial behaviors, and financial literacy among employees of private and public sectors. Furthermore, the association between financial behaviors, financial literacy, and demographics with FWB was analyzed using structural equation modelling (SEM). Finally, the study evaluated the difference in the path to FWB among public and private sector employees by splitting the data into two groups. The results indicated that financial behavior was the strongest predictor of financial wellbeing. Amongst the various responsible financial behaviors measured in the study, making correct product choice, active savings, and spending restraint were the significant factors. Further, the results demonstrated that there was no statistically significant difference in the mean subjective FWB score among the private and public sector employees. However, the pathways to achieving subjective financial wellbeing were not the same among the two groups.